Lipid hydration and mobility: an interplay between fluorescence solvent relaxation experiments and molecular dynamics simulations - Jurkiewicz, P; Cwiklik, L; Jungwirth, P; Hof, M (Biochimie, 2012)
Fluorescence solvent relaxation experiments are based on the characterization of time-dependent shifts in the fluorescence emission of a chromophore, yielding polarity and viscosity information about the chromophore's immediate environment. A chromophore applied to a phospholipid bilayer at a well-defined location (with respect to the z-axis of the bilayer) allows monitoring of the hydration and mobility of the probed segment of the lipid molecules. Specifically, time-resolved fluorescence experiments, fluorescence quenching data and molecular dynamic (MD) simulations show that 6-lauroyl-2-dimethylaminonaphthalene (Laurdan) probes the hydration and mobility of the sn-1 acyl groups in a phosphatidylcholine bilayer. The time-dependent fluorescence shift (TDFS) of Laurdan provides information on headgroup compression and expansion induced by the addition of different amounts of cationic lipids to phosphatidylcholine bilayers. Those changes were predicted by previous MD simulations. Addition of truncated oxidized phospholipids leads to increased mobility and hydration at the sn-1 acyl level. This experimental finding can be explained by MD simulations, which indicate that the truncated chains of the oxidized lipid molecules are looping back into aqueous phase, hence creating voids below the glycerol level. Fluorescence solvent relaxation experiments are also useful in understanding salt effects on the structure and dynamics of lipid bilayers. For example, such experiments demonstrate that large anions increase hydration and mobility at the sn-1 acyl level of phosphatidylcholine bilayers, an observation which could not be explained by standard MD simulations. If polarizability is introduced into the applied force field, however, MD simulations show that big soft polarizable anions are able to interact with the hydrophilic/hydrophobic interface of the lipid bilayer, penetrating to the level probed by Laurdan, and that they expand and destabilize the bilayer making it more hydrated and mobile.
Keywords: fluorescence; lipidy; rozpouštědla; voda; Molecular Dynamics Simulation; Lipid Bilayers; Fluorescence; Water; simulace molekulární dynamiky; lipidové dvojvrstvy; Lipids; Solvents